An Exploratory Qualitative Study Examining the Social and - Barry J. Gibson, BSc, MMedSc, PhD; Jackie Drennan, BSc; Sarah Hanna, BSc; (Blackwell Synergy, 2000)
This study aimed to provide a description of the psychosocial process involved in regular dental attendance. Methods: The study design was a qualitative cross-sectional study using unstructured and semistructured interviews and observations of regular dental visits